ACKNOWLEDGEMENT TO REVIEWERS 2018-2020 (Latin American Journal of Sedimentology and Basin Analysis, 2020)
The Editorial Board of the Latin American Journal of Sedimentology and Basin Analysiswould like to express its gratitude to the colleagues who acted as reviewers of themanuscripts processed during the period 2018-2020.